Effects of classroom temperature and humidity on student learning performance: an experimental study using sensor-based monitoring - Kirkil, Gokhan (Frontiers in Built Environment, 2025)
This study investigates the relationship between classroom thermal environment and student learning performance in a controlled university setting using Arduino-based temperature and humidity sensors. The experiment was conducted over 2 weeks with 53 undergraduate students at controlled temperatures of 20 °C and 27 °C. Results demonstrate significant correlations between student thermal satisfaction, GPA, and learning outcomes. Multiple regression analysis reveals that thermal environment satisfaction and student GPA together account for 23.15% of the variance in student grades (p < 0.001). Students reporting higher thermal satisfaction achieved better exam performance and maintained higher motivation levels. The study employed a 5-point Likert scale questionnaire to assess thermal perception and learning motivation. While limitations include the absence of mean radiant temperature measurements and short study duration, findings suggest that maintaining optimal classroom thermal conditions (20 °C–22 °C) is crucial for academic performance. The sensor-based monitoring system proved effective for real-time thermal environment assessment in educational settings.